Impact of economic sentiment and economic policy uncertainty on travel and leisure stock return - Hadood, Abobaker Al Al; Irani, Farid (Emerald Group Publishing Ltd, 2021)
Purpose - This paper considers the role of economic sentiment and economic policy uncertainty (both domestic and European) in explaining the changes in the contemporaneous and future travel and leisure stock index returns in top European Union (EU) tourism destinations, namely, in France, Germany, Spain and the UK. Design/methodology/approach - The authors conducted the ordinary least square (OLS) regression estimations to investigate the impact of changes in economic sentiment and economic policy uncertainty on travel and leisure stock returns. Furthermore, the authors used predictive regressions to determine whether economic sentiment and economic policy uncertainty are useful predictors over the short- or medium-term for travel and leisure stock returns. Findings - Empirical results revealed that, in France and Spain, the changes in regional economic sentiments predominantly and positively affected travel and leisure stock index returns. Also, results indicated that changes in European economic sentiment have a strong positive effect on the future travel and leisure stock returns in Spain and the UK over the short run, while in France, changes in European economic policy uncertainty have a weak negative effect on the future travel and leisure stock returns over the medium-term. Research limitations/implications - This paper provides valuable practical implications for investors who trade travel and leisure stocks. Traders can use economic sentiment and economic policy uncertainty to establish arbitrageur strategies. Originality/value - This study is the first to examine the effects of economic sentiment and economic policy uncertainty (both domestic and European) on contemporaneous and future travel and leisure stock returns in a top European tourism destination.
Keywords: Economic sentiment; Economic policy uncertainty; Hospitality industry; Macroeconomic variables; Stock returns